Características da precipitação no nordeste da Amazônia através do satélite TRMM no período de 1997 a 2012 - SOUZA, Thiago Melo (2019)
This study analyzed 15 years of spatial and temporal distribution of lightning and precipitation systems and their characteristics such as reflectivity, brightness temperature and height of the precipitation systems sampled by the Lightning Imaging Sensor (LIS), Precipitation Radar (PR) e TRMM Microwave Imager (TMI) sensors onboard of the Tropical Rainfall Measuring Mission (TRMM) satellite. This dataset is organized and stored by the research group of tropical convection of the University of Utah from December 1997 to December 2012. It was selected an area bounded between 53°W to 43°W of longitudes and between 3°S to 6°N of latitudes, which was subsequently divided into six sub-areas for more detailed information. The precipitation systems were classified according to the method of Nesbitt et. al (2000), and obeying the new definition of the data proposed by Liu (2007). The precipitation features used in this work are named ALLPFS, which are all systems with rainfall pixels estimated by the 2A25 algorithm. These systems have the categories of PFS (present information of brightness temperature) and OTHPFS (without information of brightness temperature). Within the PFS, the systems are defined as those without ice signature (WOICE), with ice signature (WICE) and mesoscale convective systems (MCS). The results show that the southern regions of Pará, around Belém and Marajo Island were the ones with the highest occurrence of lightning in the Amazon region, with values exceeding 125 to 250 lightning flashes/month*km². The WOICE systems were equally frequent in all regions. The categories WICE and MCS are those which contribute most to the production of lightning over these regions. It was also observed that the electrified systems have great contribution to the estimated amount of rainfall over central and southern parts, with percentages above 45% in the area SOUTH. The monthly variation of the lightning occurrence densities in the studied area showed that the highest occurrence of lightning was found over the city of Belem during the months from January to May, peaking in March.